An Assessment of the Local Economic Development of Songkok Industry in Gresik, Indonesia - Alya Rachma Fadhillah; Muhammad Hasyim Ibnu Abbas (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The small and medium songkok industries in Gresik Regency have developed and spread to form centers, becoming superior products and objects of cultural advancement. This study aims to assess the condition of the Local Economic Development (LED) aspect, the overall condition of LED, and the LED strategy based on centers. Previous research on LED based on centers is still limited, as it only links variables without exploring the supporting aspects in more depth. This study applies a descriptive quantitative approach with RALED (Rapid Assessment Technique for Local Economic Development) data analysis using hexagonal PEL. Data were collected through LED questionnaires according to Bappenas guidelines. The results of the study showed that there were 2 aspects with very good conditions, namely Location Factors and Sustainable Development, 3 aspects of good conditions, namely Target Groups, Governance, and Management Processes, 1 aspect of poor conditions, namely Synergy and Policy Focus. Overall, the condition of LED has a good status. The strategy that needs to be applied to LED to run more effectively can be done by using the results of the analysis of the leverage factors in each aspect of LED.